Student Selection Criteria in Undergraduate Leadership Education Programs - Daniel B. Kan; Rebecca J. Reichard (Educational Considerations, 2009)
Citizens expect and deserve effective leadership in both the public and private sectors. In today’s 24/7 information access society, high profile leaders have become a source of constant scrutiny by citizens and the media demanding results and integrity on par with the enormous salaries and fringe benefits these individuals receive.
Keywords: Education; programs; leadership; dominant role; student; undergraduate